Role of coefficient of comprehensive assessment of cardiorespiratory system in diagnostics of functional state of athletes - Vanyushin, Y. S.; Khayrullin, R. R.; Yelistratov, D. E. (Theory and Practice of Physical Culture, 2017)
The research objective was to determine the coefficient of comprehensive assessment of the cardiorespiratory system in endurance athletes of different age groups, when exposed to step load. The study involved 72 male athletes of 15 to 60 years of age engaged in endurance sports. They were divided into 4 groups according to age. The quantitative analysis of the indicators of the cardiovascular and respiratory systems has revealed that the changes in the cardiorespiratory parameters vary significantly depending on the athletes` age-specific characteristics. The set load is maintained due to the mix of combinations of oxygen transport and utilization systems interacting between each other.